ANALYSIS OF EIGHTH-GRADE STUDENTS’ MATHEMATICAL CONNECTION ABILITY IN SOLVING STATISTICS WORD PROBLEMS BASED ON MATHEMATICAL ABILITY - Feliks Eka Putra Tadayu; Alfisyahra Alfisyahra; Pathuddin Pathuddin; Akhyar H.M. Tawil (JME (Journal of Mathematics Education), 2026)
This study aims to analyze students’ mathematical connection abilities in solving statistics word problems based on their levels of mathematical ability (high, medium, and low). A qualitative descriptive approach was employed involving eighth-grade students at SMPN 9 Palu. Data were collected through written tests and semi-structured interviews and analyzed using the Miles and Huberman model. The findings reveal qualitative differences in how students construct mathematical connections. High-ability students demonstrate well-structured and flexible connections by integrating statistical concepts, arithmetic operations, and real-life contexts. Medium-ability students are able to establish connections, but these tend to be procedural and lack conceptual depth. In contrast, low-ability students exhibit fragmented understanding and experience difficulties in linking concepts, representations, and real-life applications. This study highlights that mathematical connection ability is closely related to the depth of conceptual understanding rather than merely procedural competence. The novelty of this study lies in revealing distinct patterns of mathematical connections across different ability levels within the specific context of statistics word problems. The findings provide implications for designing instructional strategies that explicitly support the development of mathematical connections in classroom practice.